The uniqueness trap - Flyvbjerg, B; Budzier, A; Christodoulou, MD; Zottoli, M (Harvard Business School Publishing, 2025)
Project managers and planners are highly prone to believing that their projects are one of a kind—partly because those that seem new and distinctive are more likely to win support. But research on 1,300-plus projects reveals that few, if any, actually are unique. The problem is, the perception of uniqueness causes managers to think there’s nothing to learn from other projects, which leads them to underestimate risk, make poor decisions, and blow through budgets and schedules. The cure is to always assume that someone, somewhere has undertaken a project like yours. If you can’t find an analogue, break your project into components, which may prove comparable with other projects. Then use forecasting and other risk assessment tools to avoid biases that undermine good choices.